Kajian Teoretis tentang Kompetensi SDM Kearsipan dalam Era Kolaborasi Manusia dan Kecerdasan Buatan - Sanbein, Primus, Mus (UI Scholars Hub, 2025)
Digital transformation in the public sector has reshaped the strategic role of archival human resources (HR), shifting from administrative executors to information curators who collaborate with artificial intelligence systems. This study aims to review and synthesize theoretical frameworks relevant to defining the core competencies of archival HR in the era of Human-AI Collaboration (HAIC). A theoretical literature review method was employed, analyzing 32 academic articles and institutional documents published between 2003 and 2025. Thematic synthesis was used to identify and classify competency dimensions into three main categories: technological-adaptive competence, socio-ethical and curatorial competence, and collaborative-systemic competence. The findings indicate that strengthening archival HR competence cannot rely solely on technical skills, but must integrate reflective, ethical, and collaborative values within technology-based work systems. This study is expected to serve as a conceptual basis for the development of curricula, professional training, and contextually relevant and sustainable certification policies.